Quantum field theory and its macroscopic manifestations : Boson condensation, ordered patterns, and topological defects - Blasone, Massimo (Imperial College Press ; Distributed by World Scientific, 2011)
This book is a self-contained presentation of the quantum field theory of topological defects created during spontaneous symmetry breakdown phase transitions, with a particular emphasis on phenomenological issues of current interest.